68Ga–Prostate-Specific Membrane Antigen Uptake in a Pancreatic Neuroendocrine Tumor. (May 2020) - Luong, Thien Vinh; Iversen, Peter; Bouchelouche, Kirsten; Arveschoug, Anne Kirstine
Abstract : Abstract: We present a 60-year-old man with known prostate cancer treated with robot-assisted radical prostatectomy. Prostate-specific antigen levels did not decline accordingly, and a second 68 Ga-PSMA PET/CT demonstrated a new focus with high 68 Ga-PSMA uptake in the pancreatic tail. A subsequent CT scan did not display the lesion as a typical pancreatic tumor, and a spleen scintigraphy was also negative excluding an ectopic intrapancreatic accessory spleen. 68 Ga-DOTATOC PET/CT showed uptake in the same area of the pancreatic tail consistent with a neuroendocrine tumor. This case illustrates that neuroendocrine tumors can be important pitfalls in 68 Ga-PSMA PET/CT performed in prostate cancer patients.